Estimation Of Probable Maximum Precipitation And Its Uncertainty For Awash River Basin, Ethiopia - Mitiku, Teshome (ASTU, 2021)
Probable Maximum Precipitation (PMP) Is Theoretically Defined As The Greatest Depth Of Precipitation For A Given Duration Which Is Physically Possible Over A Given Size Storm Area At A Particular Geographical Location And At A Particular Time Of Year. PMP Is Used To Calculate Probable Maximum Flood (PMF), Which Is Used To Size The Hydraulic Structures To Minimize The Risk Of Their Failure. The Purpose Of This Study Was To Estimate The Value Of PMP Using The Frequency Factor Obtained From The Basin-Specific Enveloping Curve And Hershfield??S Chart For 1-Day, 2-Days, And 3-Days Duration, Compare The Results And Determine The Uncertainty Analysis Associated With It. In This Study 51 Awash River Basins Stations Having At Least, 30 Years Of Record Length And Having At Least 9-Month Observations Were Used And Checked For Consistency And Homogeneity Test. The Study Shows That The Maximum Frequency Factor (K) Estimated From The Statistical Equation Was 6.1 And The Maximum PMP Values Estimated From The Basin Scale For 1-Day, 2-Day, And 3-Day Durations Were 329.24mm, 681.98mm, And 796.95mm Respectively. Similarly, The 1-Day Hershfield Chart PMP Value Was Found To Be 729.3mm. This Result Clearly Indicated That Hershfield??S Chart Overestimated The PMP Value, Which Leads To Uneconomical Designs In The Awash River Basin. The Frequency Distributions Analysis Were Conducted Using Easy-Fit Statistical Computer Software To estimate The Parameters Of The Distributions. Three Statistical Goodness-Of-Fit Test Were Conducted And Generalized Extreme Value Distribution (GEV) Was Found To Be The Best Distribution Model With A Coverage Of 50.33%. The Maximum Estimated Extreme Rainfall Magnitude From Observed Daily Maximum Rainfall For 10,000 Years Return Period For 1-Day, 2-Day, And 3-Day Durations Were 315.35mm, 641.39mm, And 786.02mm Respectively. The Salas And Bootstrap Methods Were Used To Quantify The Uncertainties In PMP Caused By K,? In The Hershfield Method. The Maximum PMP Values Quantified For 24-Hour Durations Were 319.63 Mm And 283.89 Mm. However, The Design Risk PMP With Conservative Estimation Approach Is Considerably High 329.6 Mm, Which Leads To Uneconomical Investment On Irrigation/Hydraulic Structures. The Study Reveals That Regularly Updated And Reliable Estimates Of PMP With Uncertainty Is Crucial To Maintain The Sustainable Development Of Awash River Basin And Others Basins.
Estimation Of Probable Maximum Precipitation And Its Uncertainty For Awash River Basin, Ethiopia
Keywords: Hershfield, PMP, Statistical Method, Awash River Basin, Frequency Analysis, Uncertainties.; Hershfield, Pmp, Statistical Method, Awash River Basin, Frequency Analysis, Uncertainties.